Prevalence of glutathione S-transferase M1 null polymorphism in tobacco users, oral leukoplakia and oral squamous cell carcinoma patients in South Indian population: A polymerase chain reaction study - Renu Tanwar; Asha R Iyengar; K S Nagesh; Seema Patil; B V Subhash (Wolters Kluwer Medknow Publications, 2015)
Context: Tobacco abuse is a well-known risk factor for potentially malignant disorders as well as oral squamous cell carcinoma (SCC). Factors that influence tobacco-exposed individuals developing a malignancy may include a combination of total tobacco exposure and genetic susceptibility. Aim: This study was undertaken to determine the prevalence of the glutathione S-transferase M1 (GSTM1) null polymorphism in oral leukoplakia and oral SCC patients in South Indian population. Settings and Design: This case-control study was conducted in hospital setting on South Indian population. Materials and Methods: Totally, 280 subjects with a history of tobacco use, oral leukoplakia, oral SCC were included in this study. Three milliliter of blood was collected and transported under cold cycle and taken for evaluation of GSTM1 null polymorphism using Multiplex Polymerase Chain Reaction. Results and Discussion: On comparing the prevalence of GSTM1 null polymorphism among the group with subjects with habits and no oral lesions, oral leukoplakia and oral SCC, it was observed that there was a statistically significant association between GSTM1 null polymorphism and the different groups (P < 0.01). Conclusion: The lack of GSTM1 activity would make the oral tissues more susceptible to action of tobacco carcinogens and to the development of a high-grade level of dysplasia in oral leukoplakia and thereby increases the susceptibility of lesion to undergo malignant changes.